Near-Infrared Spatial Self-Phase Modulation in Ultrathin Niobium Carbide Nanosheets - Xiao, Si; He, Yi-lin; Dong, Yu-lan; Wang, Yi-duo; Zhou, Li; Zhang, Xue-jun; Wang, Ying-wei; He, Jun (Frontiers in Physics, 2021)
Spatial self-phase modulation (SSPM) as a purely coherent nonlinear optical effect (also known as Kerr effect) can support strong broadband phase modulation, which is essential for all-optical applications. Besides this, the increasing use of two-dimensional (2D) materials opens up new prospects in this field of research. In this work, we report a broadband SSPM response from 2D transition metal carbonitrides (MXenes), Nb2C, arising in the near-infrared (1500 nm) range. Based on the SSPM measurements of few-layer Nb2C nanosheets, the third-order nonlinear optical parameters of Nb2C, including the nonlinear refractive index n2 and susceptibility χ(3), were determined at 400 nm, 800 nm, 1300 nm, and 1550 nm. Moreover, the physics mechanism of the dynamic formation process of SSPM diffraction rings was exploited. The formation time of SSPM diffraction rings can be divided into two typical parts which correspond to the polarization and reorientation of 2D Nb2C nanosheets. As a proof of concept, we demonstrate the nonreciprocal light propagation at wavelengths of 1300 and 1550 nm by constructing a Nb2C/water hybrid structure. Our results reveal strong optical phase modulation of Nb2C in the infrared region, showing thus the great potential of MXene materials for use in passive photonic devices.